Les compagnies d’assurances de personnes vont-elles demeurer des institutions financières ? - Tremblay, Marcellin (Assurances)

(untitled) (HEC Montréal, 1982)
In this thought-provoking article, Mr. Marcellin Tremblay presents the problems currently facing the insurance industry in Canada. Funds available for investment are slowly dwindling owing to the movement of the insurance market toward temporary and group insurance and the tendency of large corporate groups to increasingly channel their available funds into other sectors. Moreover, the author deplores the ever-increasing involvement of government which prevents Life assurance from fully assuming its role of capital supplier to a market which, in the years to come, will have great need of such funds.